Effect of NPK and boron on growth and yield of early cabbage (Brassica oleracea L. var. capitata) (IASH Indian Journal of Arid Horticulture, 2025)
The thirteen treatment combinations of NPK and boron fertilizers were evaluated with three replications under randomized block design during July 2023 to December 2023. The results exhibited significant effect of various treatment combinations on growth, yield of cabbage. Maximum plant height (21.20 cm, 31.67 cm and 36.87 cm on 30, 60 DAT and at harvest, respectively), number of non-wrapped leaves per plant (10.53, 14.13 and 17.87 on 30, 60 DAT and at harvest, respectively), leaf area at harvest (288.17 cm2), leaf length (28.10 cm), leaf width (21.47 cm), plant spread at harvest (71.10 cm), with minimum days taken to head harvest (80.30 DAT) and maximum polar diameter of head (13.80 cm), equatorial diameter of head (15.80 cm), fresh weight of head (931.70 g), yield per plot (13.05 kg) and yield per hectare (230.05 q/ ha) were recorded in treatment T13 (NPK 125% + boron 15 kg/ha) compared to rest of treatments, while minimum days taken to head formation (47.83 DAT) was found in T12 (NPK 125% + boron 10 kg/ha). Lowest values for these parameters were recorded under treatment T1 (Control), in which no fertilizers had been applied.